On the Doppler effect in radar - Ryazantsev, O.V.; Мarchenko, S.V.; Kulik, M.V. (Radiotekhnika, 2021)
The possibilities of simultaneous use of the longitudinal and transverse Doppler effects have been analyzed, and expressions have been derived for the corresponding beat frequencies between the emitted and received signals. As a rule, only the longitudinal Doppler effect is used in modern radio engineering systems, which makes it possible to determine the radial component of the object's speed. In addition, there are situations for which it is generally impossible to determine the speed of an object without taking into account the transverse Doppler effect. The authors analyze the fundamental possibilities of improving the functioning of radar stations that simultaneously use both types of Doppler effects – longitudinal and transverse ones – making it possible to determine the total speed of the observed object in any situations. The authors have analyzed the longitudinal and transverse Doppler effects for the case of a moving emitting object, derived expressions for the Doppler shift and expressions for the beat frequency in the case of an active radar station for both types of Doppler effects, which make it possible to obtain the value of the object's speed in any situations. Variants of determining the total speed of a moving object have been proposed, accounting the determination of its radial and tangential components. Idealized situations in which only one of the Doppler effects appeared have been considered.